Bio-Gel Formation Through Enzyme-Induced Carbonate Precipitation for Dust Control in Yellow River Silt - Jingwei Zhang; Hualing Jia; Jia Li; Xuanyu Chen; Lei Wang; Shilong Wang; Lin Liu (Gels, 2025)
This study explored the enzymatic formation of gel-like polymeric matrices through carbonate precipitation for dust suppression in Yellow River silt. The hydrogel-modified EICP method effectively enhanced the compressive strength and resistance to wind–rain erosion by forming a reinforced bio-cemented crust. The optimal cementation solution, consisting of urea and CaCl2 at equimolar concentrations of 1.25 mol/L, was applied to improve CaCO3 precipitation uniformity. A spraying volume of 4 L/m2 (first urea-CaCl2 solution, followed by urease solution) yielded a 14.9 mm thick hybrid gel-CaCO3 crust with compressive strength exceeding 752 kPa. SEM analysis confirmed the synergistic interaction between CaCO3 crystals and the gel matrix, where the hydrogel network acted as a nucleation template, enhancing crystal bridging and pore-filling efficiency. XRD analysis further supported the formation of a stable gel-CaCO3 composite structure, which exhibited superior resistance to wind–rain erosion and mechanical wear. These findings suggest that gel-enhanced EICP represents a novel bio-gel composite technology for sustainable dust mitigation in silt soils.